Breeding Efforts on Wild Honey Bee Apis cerana Fabr. within Coconut Plantations in Padang Pariaman, West Sumatra. Issue 1 (May 2021) - Jasmi,; Putra, D P; Syarifuddin,; Herwina, H; Janra, M N
Abstract: In order to maximize the potential of wild honey bee Apis cerana, there have been ongoing breeding efforts conducted in three coconut plantations in Padang Pariaman, West Sumatra. The searching for wild honey bee colonies was performed in potential sites in Lancang, Batu Gadang and Pakandangan Villages. There were 20 colonies found in the wild and relocated using hive-to-stub method; 10 colonies were then bred in its original sites while other 10 stubs transferred into farm located in Pakandangan Village. To support the breeding efforts, there was inventory survey carried out at the surrounding of breeding farms to list plants that are food sources for honey bee. From total 60 bee hives found, 32 of them built inside the hollow of dead timber, 18 nests existed in living tree crevices and other 10 nests in various hollowing structures. The successfulness of breeding effort using hiving method before transferred to distance farming location reached 76.66%, much higher than letting the stubs in the original location of wild nests (23.34%). Number of honey combs grew on the first month after transferred was variable between 3-9 frames and 124 frames (35.38%), the breadth of comb up until 75%. Plants for food sources were enlisted until 65 species, in which 20 of them categorized as cultivated and year-round flowering plants.